PENGEMBANGAN MEDIA PEMBELAJARAN FLASH CARD BERBAHAN LIMBAH SERABUT KELAPA PADA MATERI OPERASI HITUNG BILANGAN BULAT DI KELAS IV SDN 064037 MEDAN TEMBUNG: Penelitian Pengembangan - Putri Andini; Elvi Mailani; Fahrur Rozi; Albert Pauli Sirait; Lidia Simanihuruk (STKIP Subang, 2025)
This study aims to produce valid, practical and effective flash card learning media made from coconut fiber waste on integer arithmetic operation material on multiplication and division of tens and hundreds in grade IV-B of SDN 064037 Medan Tembung. This study is a Research and Development (R&D) using a 4D development model consisting of Define, Design, Development and Disseminate. The subjects of this study were 20 students of grade IV-B of SDN 064037 Medan Tembung. The data analysis technique in this study was qualitative data obtained from interviews, responses and suggestions from media validators, materials, and education practitioners (teachers). While quantitative data were obtained from questionnaires given to media experts, material experts, education practitioners and student response questionnaires. The results of the study showed that the validity assessment by media experts (lecturers) obtained a percentage of 92% with the criteria